Meningkatkan Kemampuan Berhitung Melalui Metode Pembelajaran Karyawisata Pada Anak Usia 5-6 Tahun di TK Aisyiyah 1 Sadang - Hastuti, Hesti; Hidayah, Nahdiyah (Pimpinan Cabang Muhammadiyah Kramat Jati, 2024)
Children's abilities, both cognitive abilities and other abilities, still need to be developed. Including the ability to count, the basic ability to understand counting numbers 1-10 in children needs to be developed. It's just that sometimes there are obstacles in developing children's abilities. Concrete learning for children under the age of 5-6 years is one of the factors that must be considered, therefore field trips are the method used in learning in this research. This type of research is classroom action research carried out at Kindergarten Aisyiyah 1 Sadang. The results of this study showed that there was an increase in children's numeracy skills from pre-action, cycle 1 to cycle 2. In pre-action, the percentage of children's numeracy ability was only around 31%, then in cycle 1 it increased to 51% and in cycle 2 it increased to 83%.